Production of alpha-amylase by immobolized bacillus subtilis in polymeric polyhipe matrix - Jimat, Dzun Noraini (2012)
The microcellular polymer known as polyHIPE polymer (PHP), with modified physico-chemical characteristics, was developed as a cell matrix for the immobilization of the starch-degrading bacterium, Bacillus subtilis. A suspension of B. subtilis spores were inoculated into a synthesized PHP matrix which chemically modified and this PHP matrix was named sulphonated PHPs (SPHPs). These inoculated spores were then activated by supplying continuously well-aerated culture medium (LB medium) and placed in a 370C room for 24h incubation. The growth and enzyme productivity data were evaluated and compared. Three different pore and interconnect sizes of SPHPs were evaluated; 42.0